Effect of centella asiatica against gram negative bacteria - Mimi Azuana, Wagimon
Centella asiatica (C. asiatica) is a well-known herb used in traditional medicine for treatment of a wide range of diseases. In this research, crude extract from different parts of C. asiatica extracted with two different solvents; methanol and water, were assessed for antibacterial activity against Gram negative bacteria, Helicobacter pylori (H pylori) and Escherichia coli (E. coli). The determination of minimum inhibitory concentration (MIC) was performed using microbroth dilution method. The MICs values for H pylori were 0.04 mg/ml and 0.16 mg/ml for methanolic and water leaves crude extracts, respectively, 0.16 mg/ml and 0.04 mg/ml for methanolic and water stem extracts, respectively and 0.04 mg/ml for both methanolic and water root extracts. The MICs values for E. coli were 0.01 mg/ml and 0.02 mg/ml for methanolic and water leaves extracts, 0.01 mg/ml and 1.25 mg/ml for methanolic and water stem extracts while 0.63 mg/ml and 1.25 mg/ml for methanolic and water root extract respectively. The MICs values for positive controls, clarithromycin and ampicillin, were 0.16 mg/ml and 0.01 mg/ml, respectively. Generally, all the C. asiatica extracts had a promising antibacterial effect against these bacteria.